Sex workers: starting and maintaining the profession (Research, Society and Development, 2020)
Objective: to know the insertion and permanence of sex workers in the profession. Methodology: this is a qualitative, exploratory and descriptive research, which was carried out with ten sex workers in 2015, through semi-structured interviews, participant observation and field diary, in the city of Pelotas-RS. The data obtained were grouped and analyzed using Minayo's thematic analysis. Results: the participants recognize the activity they perform as a job. They started prostitution due to financial issues, lack of job opportunities, intrafamily violence in childhood and not accepting their bodies. They routinely suffer prejudice, but have support from family members. They use the internet as a way of protection against stigma. Many are willing to leave the profession, yet encounter several obstacles. Conclusion: sex workers suffer from a lack of legal, social, and health care support. There is an urgent need to develop public policies aimed at welcoming and addressing the demands of this portion of the population.